2010
DOI: 10.2298/ciceq100126036k
|View full text |Cite
|
Sign up to set email alerts
|

Metals distribution and particle size analysis in water and sediment of the Djetinja river and Dragica spring (Serbia)

Abstract: This paper reports the results on total metal concentration (Al, Fe, Cr, Cu, Ni and Zn) in water and sediment of the Djetinja river basin in the area of western Serbia. Samples were collected in spring season. Based on the comparison of the concentrations of all analyzed metals it is possible to differentiate two zones: zone I (sampling sites 1-4), affected by the discharge of the Dragića spring, and zone II (sites 5-8), affected by the confluence of the Dragića spring with the Djetinja river. The analysis o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…The seasonal variations of the chemical composition of surface water are generally influenced by water level (i.e., dilution), as well as by anthropogenic factors: mining, industrial, urban, and agricultural activities (Reza and Singh 2010; Zare Garizi et al 2011). Heavy metal concentrations for samples collected in summer 2009 were compared with the results collected during the spring season 2009, at the same sites, reported in (Kiurski et al 2010). It was observed that at sites S1-S4, Cu and Zn concentrations were approximately 10 to 50 times lower during the summer, while at sites S5-S8, the summer and spring values were on the same order of magnitude, as could be seen in Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The seasonal variations of the chemical composition of surface water are generally influenced by water level (i.e., dilution), as well as by anthropogenic factors: mining, industrial, urban, and agricultural activities (Reza and Singh 2010; Zare Garizi et al 2011). Heavy metal concentrations for samples collected in summer 2009 were compared with the results collected during the spring season 2009, at the same sites, reported in (Kiurski et al 2010). It was observed that at sites S1-S4, Cu and Zn concentrations were approximately 10 to 50 times lower during the summer, while at sites S5-S8, the summer and spring values were on the same order of magnitude, as could be seen in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The results from this campaign (Kiurski et al 2010) showed high concentrations of Cu and Zn in both water and sediment which required further monitoring. The results from the second sampling campaign carried out during the summer of 2009 are reported in this paper.…”
Section: Introductionmentioning
confidence: 87%
“…The lakeshore area is an important area of interception of pollutants, between lake and lake, lush vegetation. The results showed that the arsenic speciation in F1 and F2 is relative to other forms of influence is weak, and the main environmental parameters pH, OM, Eh, W-DTP, S-DTP, and Lake area is not associated with the sediment grain size, heavy metals in soil and showed obvious effect of the particle size, particle size and soil the weak correlation between heavy metals, may be due to the different particle size of sediment in different proportions to adsorption of heavy metals, less sand in soil, but soil texture in a larger proportion of heavy metal content of total contribution is large, leading to higher content of heavy metals in sediments of the study area, and on the heavy metal adsorption capacity of clay soil a large proportion of the total amount of heavy metals with smaller and smaller [35][36] . F1, F2 and weak influence itself belong to the bioavailable environment state and the Lake District, F2 (Fe/Mn oxides and hydroxides) in the presence of oxygen on the heavy metals fixation plays a leading role; in hypoxic conditions, metal sulfide plays a leading role in metal speciation, due to oxidation and reduction the rise in potential, sulfide and organic binding state of the form can be transformed into unstable F1 [37] .…”
Section: Fig 4 Correlation Plots Of the Redundancy Analysis On The Rmentioning
confidence: 94%